1995
DOI: 10.1128/jb.177.24.7125-7130.1995
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic origin of mycobacterial cell wall arabinosyl residues

Abstract: Designing new drugs that inhibit the biosynthesis of the D-arabinan moiety of the mycobacterial cell wall arabinogalactan is one important basic approach for treatment of mycobacterial diseases. However, the biosynthetic origin of the D-arabinosyl monosaccharide residues themselves is not known. To obtain information on this issue, mycobacteria growing in culture were fed glucose labeled with 14 C or 3 H in specific positions. The resulting radiolabeled cell walls were isolated and hydrolyzed, the arabinose an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 19 publications
0
43
0
Order By: Relevance
“…All reproducible results now suggest that no sugar nucleotide of D-arabinofuranose is present in mycobacteria. The initial clue as to the precursors of D-arabinose came from feeding hexoses labeled in specific carbons to mycobacteria (9), which strongly suggested that the D-arabinose five-carbon skeleton was formed in the pentose shunt. A major step forward (10) then followed when it was recognized that membrane fractions of M. smegmatis were capable of converting pRpp to decaprenylphosphoryl-D-arabinose and, furthermore, that DPPR was an intermediate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All reproducible results now suggest that no sugar nucleotide of D-arabinofuranose is present in mycobacteria. The initial clue as to the precursors of D-arabinose came from feeding hexoses labeled in specific carbons to mycobacteria (9), which strongly suggested that the D-arabinose five-carbon skeleton was formed in the pentose shunt. A major step forward (10) then followed when it was recognized that membrane fractions of M. smegmatis were capable of converting pRpp to decaprenylphosphoryl-D-arabinose and, furthermore, that DPPR was an intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…The donor for the arabinofuranosyl residues has been shown to be decaprenylphosphoryl-D-arabinose (6 -8). The carbon atoms of the arabinosyl residue come originally from the pentose shunt (9) and specifically from phosphoribose diphosphate (pRpp) 1 (10). The first reaction in the formation of decaprenylphosphoryl-Darabinose is the transfer of ribose-5-phosphate from pRpp to decaprenylphosphate 2 (10) to form decaprenylphosphoryl-5-phosphoribose (DPPR).…”
mentioning
confidence: 99%
“…The D-arabinofuran residues (Araf) and D-galactofuran residues (Galf) are added to form the mature lipid-linked AG, and the immediate donor of the polymerized Araf is decaprenylphosphoryl-D-arabinose (DPA) contributing to AG and lipoarabinomannan (LAM) assembly [3][4][5]. Many of the enzymes catalyzing the synthesis of DPA serving as an arabinose donor in the cell wall biosynthesis have been identified [6] and utilized as the targets for the development of new drugs against TB [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The Araf portion is derived from the pentose-phosphate pathway [159][160][161]. 5-phosphoribose 1-diphosphate is transferred to Dec-P by the Rv3806c gene product [162] and the resultant Dec-P--D-5-phosphoribose is dephosphorylated to form Dec-P--D-ribose.…”
Section: Dpamentioning
confidence: 99%